Management Training On Tourism Development For Students At The Industrial May Of Al-Jabar Batam - Thandzir, Moh.; Dailami, Dailami; Pratama, Tito; Sukmamedian, Haufi; Ilham, Wahyudi; Yusuf, Abd Rahmad (JURNAL KEKER WISATA, 2025)
Management Training on Tourism Development is an educational activity that aims to increase the knowledge and skills of participants, especially MA students, in the field of tourism. This activity includes material on the basics of tourism management, destination development strategies, tourism promotion, as well as the role of the younger generation in supporting the local tourism sector. Through this training, participants are expected to be able to understand the importance of good management in supporting the progress of the tourism industry and be ready to become active actors or supporters in tourism development in their respective regions